Analisis Pengaruh Ekspor, Impor, Dan Kurs Terhadap Pertumbuhan Ekonomi Negara Anggota Asean (Periode Tahun 2012-2021) - Salfina, Lili; Syafrina, Feby (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The aim of this research is to analyze the influence of exports, imports and exchange rates on the economic growth of ASEAN member countries. This research uses a panel data regression analysis method (10 year time series data (2012-2021) multiplied by cross section data from 10 ASEAN member countries), so the number of samples is 100. The results of the research show that simultaneously there is a positive and significant influence on exports, imports and exchange rate on the economic growth of ASEAN member countries, while partially there is a positive and significant influence of exports on the economic growth of ASEAN member countries, partially there is a negative and insignificant influence of imports on the economic growth of ASEAN member countries, but partially there is a negative and significant influence of the exchange rate on economic growth of ASEAN member countries. From the research above, the main factor influencing economic growth is exports at 73.81%, meaning that exports are an important factor that ASEAN member countries are trying to increase. The results of the coefficient of determination test (R²) show that exports, imports and exchange rates influence economic growth by 49%, while the remaining 51% is influenced by other factors not discussed in this research. In supporting economic growth, the governments of ASEAN member countries are trying to maintain a balance of exports, imports and exchange rate stability by increasing production of the best products, then inviting the public to buy and use local products from each ASEAN member country.